The Effect of Authentic Leadership In Business Process Reengineering - محمد علي, شفاء محمد علي; زيدان, غادة طارق (Journal of Economics and Administrative Sciences, 2019)
Abstract  :The present study aims at identifying the status of the two research variables in the organization under study and specifying the relationship and impact of the authentic leadership with all its four branch dimensions of (self-awareness, transparent relations, balanced processing of information and the moral perspective) on business process reengineering.The basic problem of the study lies in the attempt to present a new leadership style that is more responsive to the dynamic changes surrounding it based on the authentic leadership behaviors. This is because this pattern has an impact on the nature of the organization's work and its progress.The research sought to test hypotheses related to the correlation and influence between search variables. The analytical descriptive approach was adopted mainly in the presentation, analysis and interpretation of the study information. The questionnaire was used as a main tool in collecting study data and information, as well as personal interviews conducted by the researcher with some of the sample members who represented a group of leaders and followers of the organization in question. Individual. The responses were analyzed using a set of statistical methods through the Statistical Program (SPSS).The study has arrived at a set of conclusions, the most important of which was that the managers of the organization under study are able to have a proper analytical ability and a high level of transparency. The research also made a number of recommendations, the most important of which is the need to start implementing business process reengineering methodology by forming highly experienced and efficient teams from different departments. These teams must attain a high level of intensive training to acquaint themselves with the programs approved in implementing this method and to be in line with the nature of the company's business.